Paecilomyces keratitis: a case report - Debapriya Das Choudhury; Milind Ubale; Rimjhim Baranwal; Vaibhavi Nanoty; Mayuri Patel (MGM Journal of Medical Sciences)
Ocular trauma involving vegetative matter is the most common cause of keratitis in ophthalmic practice in India, with many cases resulting in fungal keratitis or corneal ulceration. Here, we present a case of fungal keratitis due to Paecilomyces lilacinus that was successfully managed with oral and topical antifungal therapy, avoiding surgical intervention. The patient, a female, presented with a corneal abscess, conjunctival congestion, and persistent pain in her right eye after sustaining an ocular injury from vegetative matter. Based on the clinical signs, a provisional diagnosis of fungal keratitis was made, and treatment with 5% natamycin eye drops was initiated. Potassium hydroxide mount findings indicated fungal hyphae, leading to the addition of oral voriconazole due to suspected deuteromycosis. Fungal culture confirmed the presence of P. lilacinus. Gradually, the patient improved with antifungal therapy over a month without surgical intervention.